TikTok Usage Patterns and Character Formation Among Madrasah Students: Pola Penggunaan TikTok dan Pembentukan Karakter di Kalangan Siswa Madrasah - Hidayatullah , Muhamad Rifqi; Astuti, Ruli (Indonesian Journal of Education Methods Development, 2025)
General Background: The rapid expansion of digital technology has integrated social media into students’ daily lives, including platforms such as TikTok that provide entertainment and information access. Specific Background: Elementary-level Madrasah Ibtidaiyyah students increasingly use the platform after school and during leisure time, raising concerns regarding character development, particularly politeness and responsibility. Knowledge Gap: Limited qualitative evidence explains how routine usage relates to these specific character traits within the Madrasah context. Aims: This study investigates usage patterns and analyzes their relation to students’ politeness and responsibility. Results: Using interviews, observations, and documentation with fifth-grade students, findings show daily usage of one to three hours, mainly for entertainment and informational content. Positive materials such as religious and motivational videos support moral understanding and respectful behavior, while inappropriate content and prolonged viewing are associated with delayed duties and imitation of negative actions. Novelty: The study provides contextual qualitative insights linking social media habits with character indicators in an Islamic elementary school environment. Implications: Schools and parents are encouraged to guide ethical media practices, supervise screen time, and integrate character education strategies to balance digital engagement and responsibility. Keywords: Social Media Use, Student Character, Politeness Behavior, Responsibility Attitude, Madrasah Education Key Findings Highlights Daily viewing reaches up to three hours after school Constructive content supports moral awareness and respectful conduct Excessive exposure relates to postponed academic and household duties